Antithrombotische Therapie bei Lungenembolie - Ebner, Matthias; Lankeit, Mareike (DMW - Deutsche Medizinische Wochenschrift, 2020)
The present article addresses clinical challenges associated with the choice of the anticoagulant agent, the definition of the duration of anticoagulant treatment and the assessment of the risk-to-benefit ratio of prolonged anticoagulation for patients with pulmonary embolism (PE).Anticoagulation is performed with unfractionated heparin (UFH) in hemodynamically unstable patients and with low molecular weight heparins (LWMH) or fondaparinux in normotensive patients. In patients with high or intermediate clinical probability of pulmonary embolism, anticoagulation should be initiated without delay while awaiting the results of diagnostic tests. LMWH and fondaparinux are preferred over UFH in the initial anticoagulation of PE since they are associated with a lower risk of bleeding.All patients with PE require therapeutic anticoagulation for at least three months. The current 2019 guidelines of the European Society of Cardiology (ESC) recommend that all eligible patients should be treated with a non-vitamin K antagonist oral anticoagulant (NOAC) in preference to a vitamin K antagonist (VKA). In patients with active cancer, Apixaban, Edoxaban and Rivaroxaban are effective alternatives to treatment with LMWH.The decision on the duration of anticoagulation should consider both, the individual risk of PE recurrence and the individual risk of bleeding. The risk for recurrent PE after discontinuation of treatment is related to the features of the index PE event. While patients with a strong transient risk factor have a low risk of recurrence and anticoagulation can be discontinued after three months, patients with strong persistent risk factor (such as active cancer) have a high risk of recurrence and thus should receive anticoagulant treatment of indefinite duration. Given the favourable safety profile of NOACs (especially if a reduced dosage of Apixaban or Rivaroxaban is initiated after at least six months of therapeutic anticoagulation), extended oral anticoagulation of indefinite duration should be considered for all patients with intermediate risk of recurrence.
Keywords: Lungenembolie; Antikoagulation; Nicht-Vitamin-K-abhängige orale Antikoagulanzien (NOAK); Risikoabschätzung; Blutungsrisiko